Vitamin A, D, and E Levels and Reference Ranges for Pregnant Women: A Cross-Sectional Study 2017–2019 - Gao, Fan; Guo, Fanfan; Zhang, Yidan; Yuan, Yufei; Chen, Dunjin; Bai, Guiqin (Frontiers in Nutrition, 2021)
Background: In the current maternal vitamin management during pregnancy, pregnancy-specific vitamin reference ranges are lacking. This study aimed to propose pregnancy-specific vitamin reference ranges and investigate the influencing factors of vitamin levels during pregnancy. Methods: A cross-sectional study that included pregnant women from 17 cities in 4 provinces in the west of China was conducted from 2017 to 2019. A total of 119,286 subjects were enrolled in the study. Serum vitamin A, vitamin D, and vitamin E levels were measured. A multivariable linear regression model and restricted cubic spline function were used to analyze the factors related with vitamin levels. Results: The reference ranges for vitamin A, D, and E levels were 0.22–0.62 mg/L, 5-43 ng/mL, and 7.4–23.5 mg/L, respectively. A linear relationship was found between vitamin E level and age (β = 0.004; 95% confidence interval [CI], 0.0037–0.0042; p < 0.001); and a nonlinear relationship, between vitamin D (p nonlinear = 0.033) and A levels and age (p nonlinear < 0.001). Season, gestational trimester, and regions were related with the levels of the 3 vitamins in the multivariable models (p < 0.05). Conclusions: The lower limit of vitamin A during pregnancy was the same as the currently used reference value in the general population. The reference ranges of vitamins D and E during pregnancy were lower and higher, respectively, than the currently used criteria in the general population. Vitamin A, D, and E levels differed by age, season, gestational trimester, and region.